Summerhill, or A.S.Neill´ s legacy for the liberating well-made head education - Fortunato, Ivan (Revista Hipótese, 2017)
This text is a free essay that aims to share the main concepts of the work of Alexander Neill, founder of the free school called Summerhill. It can be considered a transdisciplinary product that seeks to combine the ideals of Neill’s free education with the ideas against the “banking education” of Paulo Freire and the postulates of the well-made head from the method for complexity of Edgar Morin. Throughout the essay we recalled autobiographical school experiences to exemplify and defend the need for different forms of education, such as Summerhill. It was written to provoke reflection on the current state of school education, but mostly to feed future research in favor of educational processes themselves.
Keywords: Complexity; School education; Summerhill; Freedom